The Influence of Bajo Culture in the Design of the Metkayina Tribe House in the Movie Avatar: The Way Of Water - Setiadi, Ahsan Hidayat (International Journal Labs, 2023)
This journal analyzes the influence of Bajo culture on the design of the Metkayina tribe's houses in the Avatar Film : The Way of Water using qualitative research methods, fil Analysis, including visual Bajo cultural references, and interpretative approaches. The study aims to identify Bajo cultural elements in the design of the Metkayina tribe's houses and understand the significance of Bajo culture in shaping the tribe's identity in the film. The expected findings aim to provide insights into cultural representation in visual arts.